Study on drug usage pattern of anxiolytics in psychiatric department in a tertiary care teaching hospital at Dehradun, Uttarakhand, India - Dutta, Shakti B.; Beg, Mirza A.; Bawa, Shalu; Kaur, Amanjot; Vishal, Subhash; Singh, Nand Kishore (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Psychopharmacology is a rapidly growing field, in which the number of patients is continuously increasing. Newly introduced drugs are projected as the better alternative to the traditional psychiatric medicines. The utilization and consequences on real life effectiveness and safety of antianxiety drugs in actual clinical practice need continuous monitoring. Aim of the present study was to analyze the pattern of various anxiolytic drugs prescribed to the patients in psychiatric department of a tertiary care teaching hospital. Methods: The present study was conducted by the department of pharmacology, in the department of psychiatry at SGRRIM and HS, Dehradun, for a period of 6 months from June 2016 to December 2016. Prescriptions of patients diagnosed with anxiety were analysed, using WHO drug use indicators. Results: A total of 603 prescriptions with anxiety disorder were collected. The mean age was 35.46±0.88 years. Majority of the patients were in 31-50 years age group 309 (51.24%). Male:Female ratio was 1:0.69. Disease pattern observed during the study were 177 (29.35%) generalized anxiety disorder, 147 (24.38%) depression, 99 (16.42%) obsessive compulsive disorder (OCD), 81 (13.43%) psychotic illness, 63 (10.45%) bipolar disorders and 36 (5.97%) patients categorized as others category respectively. A total of 1974 psychotropic drugs were prescribed, 654 (33.13%) antianxiety drugs, 648 (32.83%) antidepressants, 240 (12.16%) antipsychotics, 198 (10.03%) antiepileptics and 234 (11.85%) miscellaneous drugs were prescribed. 552 (91.54%) patients received monotherapy and 51 (8.46%) were given polytherapy of anxiolytics. All (100%) anxiolytics were orally prescribed. A total of 30 fixed dose combinations (FDCs) of anxiolytics were prescribed. The numbers of anxiolytics per prescription were 1.085. The anxiolytics prescribed from National Essential Medicine List 2015 were 555 (84.86%). The percentage of anxiolytics with brand names were 618 (94.5%). Conclusions: Most of the prescriptions were rational but there is a need to encourage prescribing by generic names so that more cost-effective and rational treatment can be provided to the patients.